ONYCHOMYCOSIS AND METHODS OF ITS TREATMENT (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Onychomycosis is a fungal disease of the nail tissue, a process caused by non-compliance with hygiene rules. This disease is contagious and can be transmitted even to family members. It can be associated with personal belongings and clothing (shoes). gyms, sauna, swimming pools, beauty pools, pedicure items in the salon, as well as sealed shoes. This can lead to negative consequences and adverse situations for patients.